DISTRIBUCIÓN DE ROEDORES RESERVORIOS DEL VIRUS CAUSANTE DEL SÍNDROME PULMONAR POR HANTAVIRUS Y REGIONES DE POSIBLE RIESGO EN MÉXICO - Sánchez Cordero, Víctor; Peterson, A. T.; Martínez Meyer, Enrique; Flores, Rita (Instituto de Ecología, A.C., 2005)
We determined distributions of rodent species known as reservoirs of Sin Nombre virus, causal agent for the hantavirus pulmonary syndrome (HPS). In the absence of HPS cases reported in Mexico, this study aimed to identify potential risk regions for HPS based on distributions of these rodent reservoirs. We modeled species’ ecological niches and projected them as potential distributions using point occurrence data, environmental digital maps, the genetic algorithm GARP (Genetic Algorithm for Rule-set Prediction), and GIS. We determined potential distributions of three rodents known to serve as reservoirs for Sin Nombre virus, four additional rodent species that may also play a role, as well as all Peromsycus species, considered as potential reservoirs for Sin Nombre virus or other hantaviruses in Mexico. Geographic locations of HPS cases coincided significantly with modeled potential distributions of the three principal rodent reservoirs in the United States. In Mexico, distributions of rodent reservoirs and potential rodent reservoirs covered ample geographic regions. Rural human populations potentially exposed to HPS (living under marginal housing conditions and with a geographic coincidence with reservoir distributions), were estimated at 650,000 - 1,750,000 persons. The geographic coincidence between rodent reservoirs and HPS cases in the United States suggests that areas of high risk for HPS will be related to rodent reservoir distributions in Mexico. Since Mexico holds ecological and social conditions amply appropriate for HPS outbreaks, we predict that (1) HPS cases will be detected across broad geographic regions coinciding with rodent reservoir distributions in Mexico, and (2) HPS will prove to be more frequent in Mexico than in the United States.